P PENGARUH DIGITALISASI LAYANAN TERHADAP MINAT GENERASI MILENIAL DALAM ISLAMIC SOCIAL FINANCE PADA LEMBAGA WAKAF SIDOGIRI: Abstrak, pendahuluan, bahan dan metode, hasil, diskusi dan pembahasan, kesimpulan dan saran referensi - Lely Ana Ferawati Ekaningsih (Tasharruf : Journal of Islamic Economics and Business, 2026)
This study aims to analyze the influence of service digitalization on the interest of the millennial generation in participating in Islamic social finance, especially waqf, at the Sidogiri Waqf Institution (L-KAF), considering that the national waqf literacy rate is still relatively low and the millennial generation, who are very familiar with digital technology, is a strategic segment for the sustainability of waqf collection. The method used is a quantitative approach with a survey design of 110 millennial respondents who are waqf or prospective waqf in the Pasuruan area and its surroundings, with multiple linear regression analysis techniques using four independent variables: ease of use, perceived usefulness, trust in digital platforms, and digital waqf literacy. The results show that these four variables have a positive and significant effect on the interest of the millennial generation in waqf through the L-KAF Sidogiri digital channel, with perceived usefulness as the most dominant variable, and the research model is able to explain 51.2 percent of the variation in waqf interest. The practical implications of this research are the need for L-KAF Sidogiri to strengthen its digital transaction convenience features and social media-based waqf literacy education campaigns, while the theoretical implications enrich the application of the Technology Acceptance Model (TAM) in the context of Islamic philanthropy based on Islamic boarding schools. The originality of this research lies in the combination of digital platform trust and digital waqf literacy variables specifically in a case study of Islamic boarding school waqf institutions that have not been widely studied before.